On the Extremal Properties of Open Composite Trapezoidal Formulae (Journal of Computational Mathematics, 2005)
It is found that the open composite trapezoidal formulae are the best quadrature formulae under three different senses.
Keywords: Open composite trapezoidal formula; Hölder classes; Sobolev classes; Best quadrature; Exact estimate; Iyengar inequality; Lagrange information.